Evaluation of thermally-modified calcium-rich attapulgite as a low-cost substrate for rapid phosphorus removal in constructed wetlands. (15th May 2017) - Yin, Hongbin; Yan, Xiaowei; Gu, Xiaohong
Abstract: The cost-effective and geographically available substrates are vital for the design of constructed wetlands (CWs), especially the saturated subsurface flow CWs, which are deemed as an efficient way to remove the inlet-lake phosphorus concentrations. In this study, phosphorus removal of thermally-treated calcium-rich attapulgite (TCAP) with varied particle sizes (0.2–0.5 mm, 0.5–1 mm and 1–2 mm) was assessed using batch and long-term column experiments to evaluate its feasibility as a CWs substrate. The phosphorus-bound mechanism in TCAP was identified in various initial phosphorus concentrations. Batch studies indicated that more than 95% of P can be rapidly (<1 h) removed by TCAP from solution with a concentration of 20 mg P/L, and P sorption can be well fitted by a pseudo-second-order equation. The maximum P sorption capacity of TCAP was in the range of 4.46–5.99 mg P/g, and the availability of Ca 2+ concentration might limit the P removal capacity of TCAP at high phosphorus concentrations. Both the P removal rate and capacities decreased with the increase of TCAP particle sizes. Column P removal experiments indicated that hydraulic retention time (HRT) exerts great influence on P removal performance and longer HRTs favor the dissolution of CaO in TCAP, consequently increasing the P removal rate. In a 150-day P removal experiment, TCAP removed an average of 93.1%–95.4% of the influent P with a HRT of eight hours. Both the batch and chemical extraction of the P fraction of TCAP showed that the P removed by TCAP was mainly through formation of Ca phosphate precipitation. However, the species of Ca-P precipitation formed might be varied in different phosphorus concentrations. All results indicated that TCAP can be a suitable substrate when used in CWs, and field experiments should be carried out to test its real P removal performance in the future. Graphical abstract: Highlights: TCAPs were first evaluated for feasibility as substrate of constructed wetlands. More than 95% of P can be rapidly removed by TCAPs within one hour. More than 90% of P removal was achieved in 150-day column experiment. P removal by TCAPs was mainly through formation of Ca phosphate precipitation. TCAPs can be used as a suitable candidate for substrate of constructed wetlands.